Barriers to Digital Transformation in SMEs: Insights from a Bibliometric Analysis - Loso Judijanto; I Made Adi Suwandana; Catarina Cori Pradnya Paramita (West Science Business and Management, 2024)
This paper presents a comprehensive bibliometric analysis of the current research landscape concerning digital transformation in Small and Medium-sized Enterprises (SMEs). Through a series of VOSviewer visualizations, we identify major thematic clusters, emerging research trends, unexplored opportunities, and patterns of author collaboration within the field. Our findings reveal a strong initial focus on crisis management in response to the COVID-19 pandemic, which gradually shifted towards long-term strategic issues such as business model innovation, digitalization strategies, and international market expansion. The analysis highlights under-researched areas including specific business processes and implications of digital transformation in the manufacturing sector, suggesting fruitful avenues for future research. Additionally, the study maps the collaboration networks among scholars, uncovering both strong interconnections and potential gaps that offer opportunities for new scholarly partnerships. This paper contributes to the strategic knowledge on digital transformation in SMEs by outlining the evolution of research themes over time and suggesting directions for future research collaborations to enhance the digital resilience and competitiveness of SMEs.